Building a Productive Workforce: The Role of Structured Management Practices - Cornwell, Christopher; Schmutte, Ian M.; Scur, Daniela (Management Science, 2021)
In an influential study, Bender et al. [Bender S, Bloom N, Card D, Van Reenen J, Wolter S (2018) Management practices, workforce selection, and productivity. J. Labor Econom. 36(S1):S371–S409] document consistent relationships between management practices, productivity, and workforce composition using administrative data from German firms matched to ratings of their practices from the World Management Survey. We replicate and extend their analysis using comparable data from Brazil. The main conclusions from their study are supported in ours, strengthening the view that more structured practices affect organizational performance through workforce selection across different institutional settings. However, we find that more structured management practices are linked to greater wage inequality in Brazil, relative to greater wage compression in Germany, suggesting that some of the consequences of adopting structured practices are tied to the local context. This paper was accepted by Joshua Gans, business strategy.